Isolation and Characterization of Polyhydroxyalkanoates (PHAs) Producers from Kg Batu Melintang hotspring (Journal of Tropical Resources and Sustainable Science (JTRSS), 2020)
The increasing awareness on the negative environmental impact of petroleum-based plastics has driven industries to explore more efficient biodegradable polymers for production of bioplastic. Polyhydroxyalkanoates (PHAs) is one of the potential biodegradable polymers to replace petroleum-based plastic. It is synthesized and accumulated as intracellular granules in microorganism. In this study, polyhydroxyalkanoates (PHAs) producing bacteria were successfully isolated from sediment collected from Kg. Batu Melintang hotspring. Isolation process was carried on Minimal Salt Medium (MSM) agar supplemented with excess glucose as a carbon source. Potential PHA producers were screened by using Nile Blue staining plate assay. Out of 144 bacterial isolates, 12 bacterial isolates which showed strong orange fluorescence under ultraviolet (UV) light (365nm) were selected for further identification by morphological characterization and biochemical analysis. Based on the result obtained, possible species for Gram positive rod shape bacteria B75 and B87 is Corynebacterium kutsceri meanwhile Gram negative rod shape bacteria A4, A12, A50, A68, B2, B13, B22, B31, B73 and C3 showed affiliation to Citrobacter sp., Enterobacter sp., Erwinia sp., Klebsiella sp., Proteus sp., Salmonella sp., Serratia sp., Shigella sp., and Yersinia sp.
Keywords: Biodegradable; mineral salt media; fluorescence; Nile Blue A